Medical student training and patient satisfaction in the internal medicine clinics of Imam Khomeini Hospital - T Dormohammadi Toosi (Journal of Medical Education and Development, 2016)
Introduction: The aim of this study was to investigate the effect of Medical Student Training on patients satisfaction referred to the internal medicine clinics. Methods: This is a cross sectional descriptive study. 200 outpatients referred to the internal medicine clinic Imam Khomeini Hospital were selected by convenient sampling. The participants were divided into two groups. The group which firstly visited by a specialist and the group which firstly visited by intern and then a specialist. In this study, researcher made questionnaire was used for measuring the patient satisfaction. Data were analyzed by using one-sample t-test, independent t-test and pair-t test. Results: The finding showed that patients are satisfied of the presence and performance of medical interns in clinics and they preferred to be visited by intern and a specialist rather than only by a specialist (p<0.001, t=13.55). The satisfaction scores of the patients in the areas of description of personal issues, a doctor knowledge, involvement in treatment decisions, feeling of visitor comfort and understand the patient's feeling visited by an intern were higher than those who were visited by only a doctor. Also, the mean scores of the patient satisfaction in the dimensions of asking questions, understandable given information, complete treatment, compliance of respectable and understand competence of given information in patients who were visited by only a doctor were more than the patients who were visited by an intern (p<0.05, t= 1.99). Conclusion: It can be concluded that the training medical students in internal medicine clinic of hospitals can be an effective strategy for the rate of satisfaction level of patients from their treatment.